2020
DOI: 10.1007/s00345-020-03402-w
|View full text |Cite
|
Sign up to set email alerts
|

Timing and delay of radical prostatectomy do not lead to adverse oncologic outcomes: results from a large European cohort at the times of COVID-19 pandemic

Abstract: Purpose The current COVID-19 pandemic is transforming our urologic practice and most urologic societies recommend to defer any surgical treatment for prostate cancer (PCa) patients. It is unclear whether a delay between diagnosis and surgical management (i.e., surgical delay) may have a detrimental effect on oncologic outcomes of PCa patients. The aim of the study was to assess the impact of surgical delay on oncologic outcomes. Methods Data of 926 men undergoing radical prostatectomy across Europe for interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…Nineteen studies were finally included in the present systematic review [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Table 1 summarizes the studies and their main findings.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen studies were finally included in the present systematic review [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Table 1 summarizes the studies and their main findings.…”
Section: Search Resultsmentioning
confidence: 99%
“…In contrast, Diamand et al observed no association between RP delay of more than 3 months after diagnosis with BCR (HR 0.97, 95% CI 0.91-1.04, p = 0.6) in both intermediate-and high-risk patients [26]. In agreement with these results, Gupta et al reported that there was no significant difference in 2-and 5-year biochemical recurrencefree survival (BCRFS) in both intermediate-and high-risk patients who had RP < 3 months vs. those who had between 3 and 6 months after diagnosis [22].…”
Section: Biochemical Recurrencementioning
confidence: 87%
See 3 more Smart Citations